FACTORS AFFECTING LION AIR AIRLINE LOYALTY BEHAVIOR IN INDONESIA - Rendi Ramadiyanto Utomo; Agus Salim (Management Research Studies Journal, 2021)
This study aims to analyze the factors that affect the loyalty of Lion Air airline behavior. The research design used was causality, while the type of research was quantitative research using the quesionary method. The population of this research is the students of Perbanas and some of the writer's friends who have flown with Lion Air, while the determination of the sample uses non-random sampling techniques and by purposive sampling. The research data used is primary data, obtained through distributing questionnaires to 100 respondents, conducted using purposive sampling technique. The analytical tool u sed is the correlation test, multiple linear regression, the coefficient of determination, and hypothesis testing. The results show that: (1) perceived fairness of price has no effect on behavioral loyalty, (2) service quality has a significant effect on behavioral loyalty, (3) customer satisfaction has a significant effect on behavioral loyalty (4) Based on the results of multiple linear regression tests, it shows that quality service is more dominant than the perception of price fairness and customer satisfaction in influencing the behavior of Lion Air airlines.